Clinical and molecular study of a case of severe radio-sensitivity - Ocolotobiche, Eliana Evelina (2019)
A case of a patient with a breast intraductal tumor is presented. The patient underwent surgical quadrantectomy and axillary lymph node dissection and subsequently received Anthracycline treatment and 3D radiotherapy following a standard fractionation protocol. This case was characterized by the development of grade III dermal toxicity, some associated genetic polymorphisms and DNA damage were analyzed. We concluded that radiotoxicity is a multifactorial phenotype that should be addressed in a broader context, considering not only intrinsic variables but also criteria such as breast size, body mass index and concomitant treatments, among others.